Application of unmanned aerial vehicle for risk identification in construction projects - Julca Alcántara, Ronald Antonio (2025)
This article was developed with the purpose of generating new knowledge about the use of unmanned aerial vehicles (drones) in the identification of occupational risks in construction projects in Peru. This work seeks to demonstrate the importance of unmanned aerial vehicles in preventive management, generating privileged aerial information from various work areas in reduced time and producing added value in occupational risk management compared to traditional methods. The unmanned aerial vehicle generates valuable information that allows different work areas to be examined in real time and to promptly detect substandard acts and conditions that may affect workers. Currently in Peru, there is little information on the use of unmanned aerial vehicles in occupational risk management; Therefore, this study has revealed favorable results on the relationship that exists between the unmanned aerial vehicle and risk identification. This correlation is supported by the statistical tests carried out, which establish that autonomous flight, panoramic views and Field inspections carried out by the drone are essential to identify occupational risks in construction projects.